ETHNOMATEMATICS-BASED GEOMETRY LEARNING IN ELEMENTARY SCHOOLS THROUGH TRADITIONAL FOOD MEDIA - Rofita Amelia; M. Ridwan M. Ridwan; Framz Hardiansyah (El Midad, 2025)
Mathematics learning outcomes, especially geometry, at the elementary school level still show a low level of understanding due to a less contextual and abstract learning approach. This study examines the effect of using traditional snacks as a medium for ethnomathematics-based geometry learning on student learning outcomes. This study uses a quantitative approach with a quasi-experimental design. The research sample consisted of 30 fourth-grade students divided into experimental and control groups through purposive sampling. The research instrument was a geometry learning outcome test composed of 20 questions that had been validated and tested for reliability. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests with t-tests. The results showed a significant difference between the experimental and control student learning outcomes, with the experimental group obtaining a much higher average post-test score. These findings strengthen the theory of constructivism and support the ethnomathematics approach in elementary mathematics learning. The implications of this study emphasize the importance of integrating local culture in the development of learning media to increase student engagement and deepen their conceptual understanding of mathematics. This study also opens up opportunities for further exploration related to using other cultural elements in mathematics learning at various levels of education